EFFECT OF HYPNOPRESSURE ON BREASTFEEDING SELF-EFFICACYAND BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Etik Khusniyati (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Breastfeeding Self-Efficacy (BSE) and milk production are two important components that directly influence breastfeeding success. Hypnopressure, a combination of hypnosis and acupressure, is considered capable of improving the psychological condition of mothers and stimulating the physiological mechanisms involved in the lactation process. This study aims to analyze the effect of hypnopressure on BSE and milk production in breastfeeding mothers. The study used a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 17 normal postpartum mothers selected through purposive sampling. BSE was measured using the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF), while milk production was measured using an electric pump. The hypnopressure intervention was given for seven days with a duration of 40 minutes per session. The data were analyzed using the Wilcoxon test. The results showed a significant increase in milk production, with the average volume increasing from 10.29 ml before the intervention to 58.18 ml after the intervention (p = 0.000). Similarly, the BSE score increased significantly from an average of 49.82 to 56.53 (p = 0.000). These findings indicate that hypnopressure plays a role in increasing relaxation, reducing anxiety, and strengthening hormonal responses through increased secretion of oxytocin and prolactin. This study concludes that hypnopressure is effective in increasing BSE and milk production in breastfeeding mothers. This intervention is recommended as a non-pharmacological strategy that can be integrated into midwifery services to support breastfeeding success, especially for mothers with high stress levels or low milk production.